Abrasion resistant characteristics of UHPC based on high-speed underwater method: Efficiency, process, evaluation, and mechanisms - Xuan Qiu; Jihui Zhao; Zhong Li (Journal of Materials Research and Technology)
Abrasion damage is a major cause of reduced service life in hydraulic structures such as bridge piers, dams, and hydroelectric stations. Ultra-High-Performance Concrete (UHPC) exhibits excellent abrasion resistance and has great potential for application in hydraulic engineering. However, the ASTM C1138 operates at a rotational speed of 1200 RPM, resulting in low testing efficiency and prolonged duration, making it unsuitable for evaluating the abrasion resistance of UHPC. In this study, a high-speed underwater method with a rotational speed of 4800 RPM was utilized to test the abrasion resistance of UHPC. The wear characteristics of UHPC under high-speed water flow conditions were investigated using a 3D visualization quantitative method. Additionally, the abrasion mechanism of UHPC was analyzed using nanoindentation testing, SEM, and MIP techniques. The results show that the efficiency of the high-speed underwater method is 5.6–14.5 times higher than that of the traditional underwater method, allowing for rapid simulation of the long-term abrasion process and evolution of UHPC. Under high-speed water flow impact, UHPC undergoes a process that includes surface paste erosion, gradual rupture of voids, detachment of aggregates and matrix, and the interconnection of wear pits. The wear rate is a relatively accurate indicator of UHPC's abrasion resistance, while volume loss is more suitable for evaluating the abrasion resistance of steel fiber-reinforced UHPC. The 3D visualization quantitative method is an effective tool for analyzing wear distribution patterns. The abrasion resistance of UHPC is negatively correlated with ITZ thickness and porosity.